Methods to Detect Small Molecule Inhibition of RING E3 Ligase Activity. Issue 4 (18th April 2022) - Rothenaigner, Ina; Brenke, Jara Kerstin; Schorpp, Kenji; Hadian, Kamyar
Abstract: Protein ubiquitination is an essential post‐translational modification that regulates a large number of cellular processes. This reaction is facilitated by the consecutive action of three central enzymes, i.e., E1 activating enzyme, E2 conjugating enzyme, and the E3 ligase. More than 600 E3 enzymes guarantee the specificity and selectivity of these reactions and thus represent an exciting, while highly underrepresented, class of drug targets. Specific methods can be employed to monitor their activity and thus query compound libraries for inhibitory small molecules. Here, we describe two protocols—one high‐throughput and one low‐throughput method—to detect E3 ligase activity and test small molecule modulation. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : AlphaScreen assay to measure TRAF6‐Ubc13 interaction Basic Protocol 2 : Gel‐based in vitro ubiquitination assay (K63‐linked chains)